Synthesis and Characterization of Hydrogel-Based Hyaluronic Acid-Chitosan-Allium sativum Extract for Intraperitoneal Antiadhesion Application - Widiyanti, Prihartini; Priskawati, Yolanda Citra Ayu (International Journal of Biomaterials, 2023)
Peritoneal Adhesion is a severe case that frequently occurs in patients after laparotomy surgery. Adhesions are pathological attachment that usually appears between the omentum, intestine, and abdominal wall. Several barriers are made to prevent adhesions, including liquid barriers such as sodium hyaluronate and carboxymethyl cellulose (CMC) but are fast absorbed-time hydrogel. The solid barrier has weakness of difficulty in covering all parts of the wound surface. The study aims to synthesize degradable hydrogel from N,O-Carboxymethyl Chitosan (NOCC), Aldehyde-Hyaluronic Acid, and the addition of Allium sativum (garlic oil). The best sample with the concentration of A-HA/NOCC 30 : 10 g/ml was obtained. The composite hydrogel of NOCC/AHA/Allium sativum has susceptible antimicrobial properties. In vitro cytotoxicity assay showed that hydrogel is nontoxic. The degradation time is for two weeks. The in vivo evaluation in a mouse model with an abrasion defect side was done to identify the effectiveness of the NOCC/AHA/A. sativum as antiperitoneal adhesion. Seven days after surgery, the observation of adhesion was performed. Based on all assay results, it can be resumed that the NOCC/AHA/A. sativum hydrogel possibly acts as an innovation to prevent postoperative intraperitoneal adhesion.